Level of Self Esteem among Medical Students in International Islamic University Malaysia Kuantan (IIUM) and its Association with Religiosity - Amiruddin, Amirah; Mustapa, Nurul Fitri; Hadi, Azwanis Abdul; Abidin, Muhammad ‘Adil Zainal (International Journal of Human and Health Sciences (IJHHS), 2021)
Introduction: Self-esteem is an essential aspect of wellbeing particularly for medical students who are susceptible to mental disorders. In Islam, self-esteem is built based on both revelation by Allah and human’s effort. With the increasing study in terms of religiosity and self-esteem, the role of religiosity as possible protective factor for Muslim medical students in their life, is a steppingstone towards becoming competent Muslim professionals. Objectives: This study aims to measure the level of self-esteem among medical students and its association with religiosity. Methods: This online cross-sectional study was conducted among 178 International Islamic University Malaysia (IIUM) Kuantan medical students using validated 10-items IIUM Religiosity Scale (IIUMReIS), and 10-items Rosenberg Self-Esteem Scale (RSES). Descriptive statistics was used to measure the level of self-esteem while chi-square, Mann-Whitney U test, Spearman’s correlation, univariate and multivariate logistic regression were used to explore the association between self-esteem with the predictors. Results: More than half of the students (58.5%) have a high level of self-esteem. They scored an average of 35 (IQR = 6) in terms of religiosity. Those with higher religiosity were predicted to have significantly high self-esteem (r = 0.345). Other significant factor includes, frequency of voluntary prayer where daily practice has 0.3 lower odds of having low self-esteem. (95% CI = 0.11, 0.85, p = <0.05) Conclusion: Majority of the students have a high level of self-esteem. Implications of the role of religiosity and the impact of voluntary prayer were suggested. Early and consistent strengthening of self-esteem via motivational, spiritual and religious programs may be advisable. International Journal of Human and Health Sciences Supplementary Issue: 2021 Page: S27